Assessing wave energy converters in the gulf of Mexico using a multi-criteria approach - Diaz-Maya, Miqueas; Ulloa, Marco; Silva, Rodolfo (Frontiers in Energy Research, 2022)
The wave power in the Gulf of Mexico was analyzed, using 42 years (1979–2020) of simulated data, with ERA-5 winds to force the WAVEWATCH III wave model. The model was successfully validated with three NDBC buoys, 42,055, 42,001 and 42,002. Comparison of significant wave heights obtained from the Jason-2, Cryosat-2, and Saral satellites showed good mean correlation coefficients and root mean squares. The spatial distribution of wave power was studied, as well as its seasonal variability. The region studied has moderate availability of wave power with marked seasonality. A multi-criteria MCA approach, including both sea state and wave energy converters (WECs), was then applied. Nine virtual sites were selected for the study and the AAHPA device gave best results in 7 virtual sites and the Wavestar device in the remaining two. The technology of these two devices, a system of oscillating buoys, is the most viable technology for the Gulf of Mexico.